Status of Economic Loss and Damage Caused by Climate Change in Nepal: Patterns, Impacts, and Policy Imperatives - Adhikari, Sanot; Raut, Sweccha; Basnet, Umesh; Bhusal, Bhawana; Pokharel, Anju; Bhandari, Suwash (Four Star Multidisciplinary Research Journal, 2025)
Nepal, the fourth most climate-vulnerable country in the world, is experiencing increasing economic and non-economic losses from climate-induced disasters. This in-depth analysis of available data on climate change impacts in Nepal during the period 1971-2025 shows increasing trends in economic costs as well as non-economic impacts. Recent average annual economic losses stand at 0.08% of GDP (NPR 2.78 billion) with extreme years touching 2.08% of GDP. Physical property accounts for 75% of economic loss, followed by agriculture (18%), livestock (4%), and food storage (3%). Non-economic losses comprise an average of 647 deaths every year due to climate disasters, large-scale displacement, loss of cultural heritage, and ecosystem degradation. Future scenarios project economic losses to reach 2.2% of GDP by 2050 and 9.9% by 2100 in the absence of proper mitigation. The study identifies major gaps in loss and damage assessment capacity, weak financial mechanisms, and low recovery capacity of vulnerable communities.